Evolutionary Perspectives on Enhancing Quality of Life - Larsen, Mads; Witoszek, Nina (Cambridge University Press, 2024)
This Element reviews existing literature and proposes synthesizing insights into human flourishing under multilevel selection (MLS). It approaches meaning as a reward that individuals experience when contributing to their community, using the Nordic well-being societies as examples. This title is also available as Open Access on Cambridge Core.